Patriots Day [videorecording (DVD)] - Wahlberg, Mark, 1971-; Bacon, Kevin, 1958-; Goodman, John, 1952-; Simmons, J. K. (Lions Gate Entertainment, 2017)
The story of Boston Police Commissioner Ed Davis's actions in the events leading up to the 2013 Boston Marathon bombing and the aftermath.